Long-term Results of Topical Insulin Treatment for Persistent Corneal Epithelial Defects - Júlio Almeida; Tomás Costa; Maria Vivas; Catarina Monteiro; Fernando T. Vaz; Diana Silva; Cristina Vendrell; Isabel Prieto (Journal of Ophthalmic & Vision Research)
Purpose: To evaluate the effects of topical insulin in patients with persistent corneal epithelial defects that are refractory to the standard treatment. Methods: A retrospective, hospital-based, clinical study was performed on 17 eyes of 16 patients with different types of refractory persistent epithelial defects who were treated with topical insulin. The treatment was continued until the defect either was resolved or persisted after three months. Patients’ demographic information, etiology, comorbidities, and clinical data were reviewed. The rate of epithelial healing was considered as the primary outcome measure. Results: Neurotrophic keratitis was the most common cause of persistent epithelial defects (58.8%), and within this category, herpetic eye disease was the main comorbidity (44.4%). The mean follow-up time was 17.91 months. Eleven out of fifteen eyes (77.3%) had complete improvement and only one patient did not respond to the treatment. The mean time of reepithelization for the eyes with full recovery was 31.27 days (ranging from 6 to 61 days). The best-corrected visual acuity improved significantly after treatment (P < 0.005), and there were no reports of complications or side effects during the study period. Conclusion: Our results suggest that topical insulin, due to its good safety profile, availability, and affordability, could be a good therapeutic alternative for persistent epithelial defects.